Penerapan Algoritma Dijkstra Dan Greedy Untuk Optimasi Rute Angkut Sampah Di Kecamatan Periuk - Mahfoud, Muhammad Adam Nadjib; Hidayat, Taufik; Sukrim, Sukrim; Sukisno, Sukisno; Nugroho, Asep Hardiyanto (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2024)
Abstract : The increase in population in urban areas has resulted in an increase in the volume of waste generated. This creates problems in waste management, especially in determining efficient transportation routes. This study aims to optimize waste transportation routes in Periuk Subdistrict, Tangerang City, by applying Dijkstra and Greedy algorithms. Dijkstra's algorithm is used to find the shortest path based on the minimum distance traveled, while the Greedy algorithm is used to select the path that looks most profitable at each step. Geographical data in the form of coordinates of Waste Disposal Sites (TPS) and the distance between TPS are used as input in both algorithms. The results showed that Dijkstra's algorithm produced the shortest route with a distance of 16.7 km, more efficient than the route produced by the Greedy algorithm with a distance of 24.1 km